Ex-situ Conservation of Woody Plants within the Framework of the Millennium Seed Bank Partnership in Georgia - Mikatadze-Pantsulaia, Tsira; Kolbaia, Sandro; Gogoladze, Ana; Grdzelishvili, Irakli (European Journal of Sustainable Development, 2024)
Georgian flora comprises of the vascular plants grown in wild conditions on the territory of country, comprising 185 families, 1,048 genera and 4,275 species. High endemism level of Georgian flora reflects its richness - 21% of the local flora is endemic. Nearly 10% of Georgian flora comprises of around 400 tree and shrub species. About 40 per cent of them are included in the Red List of Caucasus Endemics. Within the framework of the Millennium Seed Bank partnership, 144 populations of 131 species of trees and shrubs common in Georgia were collected at the place of natural distribution and deposited in the National Seed Bank of Georgia (NSBG) under the Global Tree Seed Bank Project (Georgia) with the funding from the Garfield Weston Foundation (2015-2019). The created genetic bank includes rare, endemic, relict, endangered and economically important species, they have food, medicine, fuel, construction, paint and other properties. This collection also comprises relict species of Colchic forests important for the study of the history of the Caucasus flora from the following genera: Rhododendron, Betula, Ruscus, Ilex, Daphne, Hedera, Laurocerasus, amongst others; The National Seed Bank is established for long-term storage of the wild plant species of Georgia. Seed duplicates from different populations of all target species of the above mentioned project are kept in the Millennium Seed Bank of the Royal Botanic Gardens, Kew, UK. In addition to the seed bank, a collection of seedlings of some of these species has been created in the collection plot of the Plant Conservation Department. Key words: ex-situ conservation, tree and shrub species, seed bank, seedlings collection.